LEVEL SHIFT AND PHASE SHIFT MODULATION FOR NINE LEVEL INVERTERS - Shweta, R.K.Padmashini (International Journal of Advanced Science and Technology, 2020)
This paper demonstrated a disparity between two techniques of modulation, both using sine wave as the reference wave. The FFT study was carried out after the correlation of voltage an current levels for the two techniques and the THD of the two techniques was addressed with the aid of the simulation carried out on MATLAB 2015 a Software. For a 9 level cascaded inverter, the two techniques were discussed. Since IGBT is highly efficient and quickly switched compared to other semiconductor switching devices. Under carrier based pulse width modulation, although there are many techniques compared to phase shift modulation method, just level shift modulation (i.e. in phase disposition (IPD)) was compared. Finally, based on the FFT analysis, the method having less THD can be used for any kind of speed control of motors.